Analisis Efektivitas Penegakan Hukum terhadap Pelanggaran Lalu Lintas oleh Anak di Bawah Umur - Asita Putri (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2026)
Traffic violations committed by minors remain a significant legal and social issue in Indonesia. The increasing number of underage children operating motor vehicles without meeting legal requirements not only violates traffic regulations but also increases the risk of road accidents that may endanger both the children and other road users. This study aims to analyze the effectiveness of law enforcement against traffic violations committed by minors, identify the factors influencing its implementation, and formulate strategies to improve legal compliance in traffic behavior. The research employs a normative legal method using a literature study approach through the examination of laws and regulations, legal doctrines, scholarly journals, and relevant previous studies. The collected data were analyzed descriptively using a qualitative approach based on the theory of legal effectiveness. The findings indicate that law enforcement regarding traffic violations by minors has not been fully effective, despite the existence of clear legal regulations prohibiting such conduct. The main contributing factors include low legal awareness among minors, inadequate parental supervision, social environmental influences, limited law enforcement facilities, and a permissive societal attitude toward underage driving. Therefore, stronger collaboration among law enforcement agencies, families, schools, and communities is necessary to enhance legal compliance and traffic safety among children.